Chester's Way - Henkes, Kevin (New York : Greenwillow Books, 1988)
Chester and Wilson had their own way of doing things, and they did everything together. When they cut their sandwiches, it was always diagonally. When they rode their bikes, they always used hand signals. If Chester was hungry, Wilson was too. They were two of a kind, and thats the way it was -- until indomitable Lilly, who had her own way of doing things, moved into the neighborhood
Accelerated Reader AR
Keywords: Mice -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship in children -- Juvenile fiction; Individual differences in children -- Juvenile fiction; Fiction; Juvenile works; Picture books; Picture books